Optimalisasi Potensi Geowisata Danau Tirta Gangga Kampung Swastika Buana, Kecamatan Seputih Banyak, Lampung Tengah - Rajiman; Yulfriwini; Ikhsan Karim; Aprizal; I Komang Andika Putra; Revo Rudita (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Lake Tirta Gangga is an artificial lake located in Central Lampung Regency, Seputih Banyak District, precisely in Swastika Buana Village. This lake has an area of ​​about 150 hectares and is used by the community for irrigation of about 3000 ha of agricultural land around the area. Lake Tirta Gangga has its own charm for local tourists to enjoy its natural beauty and scenery. However, some community activities cause the aspect of natural beauty to be reduced and cause problems in the supply of raw water for agriculture. So we need an action that can maintain the initial function of this lake and even add economic value to the community. This service aims to overcome these problems by mapping the potential of new geotourism that can be developed and managed by the community, educating the community in improving the quality and excellence / local wisdom which has an impact on increasing the economic value of the Tirta Gangga Lake area by utilizing information technology for media promotion (with drones) profile of the Lake Tirta Gangga tourist area. The benefits of this service are the mapping of new geotourism potentials that can be developed and managed by the community as well as the formation of video promotion media for the profile of the Lake Tirta Gangga tourist area which can be disseminated through internet media so that tourists can easily recognize and be interested in visit Tirta Gangga Lake.